Development of Android Mobile Learning Media Integrated Islamic Content on Human Excretion System Material (Unnes Science Education Journal, 2022)
This study aimed to produce android mobile learning media integrated with Islamic content in the Human Excretion System material that is feasible, valid and practical for students class VIII MTs students. The product is packaged in an Application Package File (.apk) format and developed using the ADDIE Research and Development model (Analysis, Design, Development, Implementation, and Evaluation) method. The application contains Objectives, Materials, Simulations, and Evaluations. Apps are rated by materials experts, media experts, and teachers. In addition, the product has gone through three stages of evaluation for students in class VIII junior high school students involving three students in a one-to-one trial, nine students in a small-scale trial, and 35 students in a field trial. The validity of the media shows that at 3.27, it can be classified as "very good", 3.42 for practicality results and categorized as "very good", and 3.24 for student responses and classified as "good".